1983
DOI: 10.1677/joe.0.0960499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolactin on steroid production by human luteal cells in vitro

Abstract: The effects of prolactin on steroidogenesis were studied in dispersed luteal cells prepared from human corpora lutea of the menstrual cycle. Prolactin, at concentrations of 0.1-1000 ng/ml, had no effect on progesterone production by luteal cells during short-term incubation (3 h). However, in two out of five corpora lutea, higher concentrations of prolactin (100 and 1000 ng/ml) significantly reduced the oestradiol-17 beta production induced by human chorionic gonadotrophin (hCG; 10 i.u./ml); lower doses of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…This was also reported in the more recent study of Tan & Biggs (1983) who examined enzymatically dispersed human luteal cells.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This was also reported in the more recent study of Tan & Biggs (1983) who examined enzymatically dispersed human luteal cells.…”
Section: Discussionsupporting
confidence: 78%
“…In their study of human CL using enzymatically dispersed cells, Tan & Biggs (1983) reported that in two of the five CL examined, high prolactin levels inhibit hCG-induced oestradiol production but have no effect on progesterone. This was not found in the present study, and may be an artifact due to the method of cell dispersion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McNatty et al (1974) demonstrated that a high concentration of PRL in the follicular fluid may depress the progesterone secretion by granulosa cells. Higher concentrations of PRL may reduce 17b-estradiol production induced by hCG in human luteal cells in vitro (Tan & Biggs 1983). On the other hand, the production of progesterone and estrogen was higher when hCG was applied in combination with PRL than when hCG only was applied (Hunter 1984).…”
Section: Prolactin Secretion Patterns In Reproductionmentioning
confidence: 99%
“…An important feature is luteal phase (LP) insufficiency [6,7], but it has not yet been fully established whether this is due to a direct luteolytic effect of hyperprolactinemia [8] or is a consequence of a disturbance of the hypothalamic-pituitary axis [9,10]. Prolactin (PRL) modulates steroidogenesis of human ovarian cells by exerting either a stimulatory [11,12] or an inhibitory [8,[13][14][15] effect. Some reports have indi cated a lack of a direct effect of PRL on human ovarian tissues [16,17] but the human ovary has also been shown to have specific receptors for PRL, suggesting that PRL may have a direct effect on ovarian function [18][19][20].…”
Section: Introductionmentioning
confidence: 99%